Quality Control for Distributed Video Coding Based on Wavelet - Lan Bai (2012 8th International Conference on Wireless Communications, Networking and Mobile Computing, 2012)
To keep constant video quality is one of the key issues in video coding application, so quality control is a crucial while difficult subject for either the traditional video coding or distributed video coding. In this paper, we propose a quality control algorithm through using distortion quantization (DQ) model to decide quantization step for the next Wyner-Ziv frame with the purpose of the distortions between key frame and Wyner-Ziv frame are approximative and so we can get constant video quality. The RD performance is compared while with and without this algorithm. It shows that at the sacrifice of the PSNR (rather small) averagely overall, the proposed quality control solution obtains more constant video quality than the codec without any quality control scheme.